Legal Status of Wills Not Reported by Notaries to the Will Registration Center (Case Study: Decision Number 91/Pdt/2021/PT.PTK) - Verdilla, Utami Dinda; Hasbi, Muhammad; Mannas, Yussy Adelina (jurnal.unprimdn.ac.id, 2026)
This study examines the legal standing of a notarial will deed not reported to Indonesia's Central Will Registration Center, with a case study of Pontianak High Court Decision No. 91/Pdt/2021/PT.PTK. Using a normative juridical method—statutory, conceptual, and case approaches—the study addresses two questions: (1) what is the regulatory framework for will reporting by notaries? and (2) what were the judges' considerations in Decision No. 91/Pdt/2021/PT.PTK? The study finds that the reporting obligation rests on a hierarchical normative structure: the Civil Code as material law, Law No. 30/2004 as amended by Law No. 2/2014 on the Notary Profession (UUJN) as the obligation-setter, and Minister of Law Regulation No. 16/2025 as the technical instrument. Despite this clear framework, the Pontianak High Court held that a notarial will retains its evidentiary force as an authentic deed even when not reported to the Will Registration Center, because reporting is an administrative obligation of the notary and its omission does not constitute a ground for nullification under existing law. This creates a normative gap that weakens legal certainty for heirs and beneficiaries.